2022
DOI: 10.3390/cells11060947
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs of Extracellular Vesicles in Tumor Angiogenesis: From Biological Functions to Clinical Significance

Abstract: Extracellular vesicles (EVs) act as multifunctional regulators of intercellular communication and are involved in diverse tumor phenotypes, including tumor angiogenesis, which is a highly regulated multi-step process for the formation of new blood vessels that contribute to tumor proliferation. EVs induce malignant transformation of distinct cells by transferring DNAs, proteins, lipids, and RNAs, including noncoding RNAs (ncRNAs). However, the functional relevance of EV-derived ncRNAs in tumor angiogenesis rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 141 publications
0
9
0
Order By: Relevance
“…Our results support existing data by showing that cancer cells reprogram their surroundings into a tumor-promoting microenvironment via the secretion of EVs [ 57 ]. In order to create their own vascular system, tumors change their microenvironment from an antiangiogenic to a proangiogenic one via a process termed “angiogenic switch” [ 29 , 58 ]. Our report supports the premise that EVs may be specifically involved in such a cancer-related angiogenic switch; moreover, this is the first study to demonstrate the role of GC-EVs in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support existing data by showing that cancer cells reprogram their surroundings into a tumor-promoting microenvironment via the secretion of EVs [ 57 ]. In order to create their own vascular system, tumors change their microenvironment from an antiangiogenic to a proangiogenic one via a process termed “angiogenic switch” [ 29 , 58 ]. Our report supports the premise that EVs may be specifically involved in such a cancer-related angiogenic switch; moreover, this is the first study to demonstrate the role of GC-EVs in this process.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are mediated by the content of EVs, including RNA (mRNA, miRNA, and other RNAs), proteins, and lipids [ 26 , 27 ]. While knowledge on the role of tumor-derived EVs in angiogenesis is expanding [ 28 , 29 ], research on the role of GC-derived EVs (GC-EVs) in angiogenesis is still in its early stages and mainly focuses on EVs-derived miRNA [ 30 , 31 ]. We characterized the angiogenic protein content of GC-EVs, demonstrating their proangiogenic in vivo and in vitro effects, specifically through ANG2.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EVs circRNAs can modulate the permeability of endothelial cells, thereby facilitating the metastasis of cancer cells 32 . In conclusion, various RNAs in EVs play important regulatory roles in angiogenesis by targeting different molecules 33 …”
Section: Evs Affect Various Processes Of Npcmentioning
confidence: 97%
“…Other studies have shown that dendritic cells take up circulating EVs from other dendritic cells, and their cargo proteins are processed and presented as antigens, playing a role in immune regulation [ 33 , 34 ]. Among other pathological conditions they are involved in, cancer has received the most attention [ 35 , 36 ], but EVs also play a role in neurodegenerative diseases such as Alzheimer’s [ 37 ] and cardiovascular diseases such as atherosclerosis [ 38 ], as well as infectious diseases such as HIV-1 infection [ 39 ].…”
Section: The Interest Of Evs In Solid Organ Transplantationmentioning
confidence: 99%